2014
DOI: 10.22452/ajap.vol7no1.3
|View full text |Cite
|
Sign up to set email alerts
|

Operationalising Enterprise Risk Management (ERM) Effectiveness

Abstract: Studies on ERM effectiveness appear to suffer from the same catastrophic dilemma as that of organizational effectiveness. To the best of the author's knowledge, very little research has been done on the effectiveness of ERM in managing risks. Based on the guidance from the COSO (2004) framework and the existing literature coupled with the insights gathered from semi-structured interviews, the current article aims to demarcate a workable model, and, thereafter, an instrument to be operationalized in ERM effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Top management is necessary for effective risk management (Kaplan & Mikes, 2014). Effectiveness of ERM (Togok, 2016), risk management (Banasadegh, Riahi, & Davari, 2014;Cooper, Faseruk, & Khan, 2013;Maina, Mbabazize, & Kibachia, 2016;Ngundo, 2014), security risk management (Zafar et al, 2011), and risk management success (Agoi, 2013) are all directly correlated with top management support. Academic studies have indicated that one of the most important success factors for risk management is upper management support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Top management is necessary for effective risk management (Kaplan & Mikes, 2014). Effectiveness of ERM (Togok, 2016), risk management (Banasadegh, Riahi, & Davari, 2014;Cooper, Faseruk, & Khan, 2013;Maina, Mbabazize, & Kibachia, 2016;Ngundo, 2014), security risk management (Zafar et al, 2011), and risk management success (Agoi, 2013) are all directly correlated with top management support. Academic studies have indicated that one of the most important success factors for risk management is upper management support.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies looked at how top management support directly affects the dependent variables (Ngundo, 2014;Ranong & Phuenngam, 2009). On the other hand, several studies looked at the direct or indirect effects of top management support on the variables being studied (Togok, 2016). The results of a study by Togok (2016) showed that organizational culture has an indirect impact on ERM effectiveness, but tone from the top also has a substantial direct impact.…”
Section: Discussionmentioning
confidence: 99%
“…Structured questionnaires administered to the owners/managers of 400 SMEs selected in Lagos State were used to generate primary data for the study. Various sections of the questionnaire were adapted from the scales used by previous researchers (Sefiani, 2013;Togok, Isa & Zainuddin, 2014;Lekhanya, 2016 Copies of the questionnaires were administered by the researchers with supports from three research assistants. A total of 400 questionnaires were administered out of which 313 copies were collected and found useful for the study.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it helps to identify potential events capable of affecting the enterprise and manage them to ensure that they fall within ERM Framework by the Committee of Sponsoring Organisations of the Treadway Commission (COSO, 2004) is adopted by this study. Togok, Isa and Zainuddin (2014) in their study had engaged this framework to operationalise ERM effectiveness. The framework comprises of eight interrelated functions through which organisations can effectively manage their risks to facilitate survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation